Obstacles To Literary Translation: Challenges and - payam abbasi; hoseyn vahid dastgerdi (Matn/Pizhūhī-i Adabī, 2005)
The translator of a literary text has to observe the semantic sense of the words, the weight, the cultural setting, and other technical features of the original text to yield an acceptable translation in the TL. The accomplishment however is not that easy, for the translator meets some major impediments in performing the task. A translator who is familiar with different critical approaches, a translator needs to, first, interpret the text and then see how the message can be conveyed in the TL, from which the reader is likely to elicit the same interpretation. Being open to interpretation on different levels, a literary text challenges the translator who has to explore the true meaning and reshape it in another system. The translator of a literary text should also interpret the text according to the cultural setting it was written in. The dominant ideology of the time does not leave literature unaffected and much of the semantic weight of the text might have been shaped accordingly. The style and structure of a literary text are different from those of the ordinary language because the intentions lying behind them are different and each style is correspondent with the purpose of the writer. Finding proper equivalences is of great importance. Due to the sundry implications and connotations words have, translators of literary texts need to find equivalences that are the most precise and capable of conveying the implied meanings. Sincere attempt is needed to transfer culture-bound idioms and proverbs from SL to TL. Literary texts are abundant with idioms and proverbs that are meaningful in the context of the culture they are part of. With all such things in mind, a satisfactory literary translation should crave creativity and knowledge on the side of the translator if the unity and pleasure of literary texts is to be kept and conveyed.